Genome-Wide Analyses Reveal Genes Subject to Positive Selection in Pasteurella multocida - Cao, Peili; Guo, Dongchun; Liu, Jiasen; Jiang, Qian; Xu, Zhuofei; Qu, Liandong (Frontiers in Microbiology, 2017)
Pasteurella multocida, a Gram-negative opportunistic pathogen, has led to a broad range of diseases in mammals and birds, including fowl cholera in poultry, pneumonia and atrophic rhinitis in swine and rabbit, hemorrhagic septicemia in cattle, and bite infections in humans. In order to better interpret the genetic diversity and adaptation evolution of this pathogen, seven genomes of P. multocida strains isolated from fowls, rabbit and pigs were determined by using high-throughput sequencing approach. Together with publicly available P. multocida genomes, evolutionary features were systematically analyzed in this study. Clustering of 70,565 protein-coding genes showed that the pangenome of 33 P. multocida strains was composed of 1,602 core genes, 1,364 dispensable genes, and 1,070 strain-specific genes. Of these, we identified a full spectrum of genes related to virulence factors and revealed genetic diversity of these potential virulence markers across P. multocida strains, e.g. bcbAB, fcbC, lipA, bexDCA, ctrCD, lgtA, lgtC, lic2A involved in biogenesis of surface polysaccharides, hsf encoding autotransporter adhesin, and fhaB encoding filamentous haemagglutinin. Furthermore, based on genome-wide positive selection scanning, a total of 35 genes were subject to strong selection pressure. Extensive analyses of protein subcellular location indicated that membrane-associated genes were highly abundant among all positively selected genes. The detected amino acid sites undergoing adaptive selection were preferably located in extracellular space, perhaps associated with bacterial evasion of host immune responses. Our findings shed more light on conservation and distribution of virulence-associated genes across P. multocida strains. Meanwhile, this study provides a genetic context for future researches on the mechanism of adaptive evolution in P. multocida.